Волинська губернія в оперативних концепціях французького Генерального штабу напередодні війни 1812 р. - Homich, Dmitro; Хоміч, Дмитро (Східноєвропейський національний університет ім. Лесі Українки, 2013)
У статті розглянуто стратегічну роль волинських земель у планах наполеонівського військового командування напередодні франко-російської війни 1812 р. Показано основні джерела формування уявлень французького Генерального штабу про Волинь під час підготовки нападу Наполеона на Російську імперію.Today, in spite of recent celebration of 200-years-old anniversary of victory of the Russian empire in opposition with Napoleon’s France, contemporaries rarely reminisce that Volyn was the unique Ukrainian territory which the active battle actions of the outlined period were conducted within the limits of. In this article the strategic role of Volyn earths is examined in the plans of the French General staff on the eve of war 1812 years. The basic sources of forming of presentations of the Napoleon’s military command are rotined about Volyn during preparation of attacking the Russian empire, it is indicated on the decision role of the Polish informants in the process of creation of general appearance of the Volyn edge in perception of Bonapart and his nearest surroundings.
Volyn Province in Operative Conceptions of the French General Headquarter on the Eve of War 1812 Years
Keywords: війна 1812 р.; Волинь; меморандуми; австрійці; саксонці; war 1812 years; Volhyn; «memorandum»; austrians; saxons